Criminalidade violenta e contradições socioespaciais na cidade de Uberlândia-MG - Santos, Márcia Andréia Ferreira (2012)
This research aimed to identify and interpret the factors that contribute to the rapes, murders and robberies incidence at Uberlândia (Minas Gerais State, Brazil). The study also examined some events related to drugs, such drug bust (trafficking and use), arrests of traffickers and users with more than eighteen years old and busting people under eighteen years old involved in drug trafficking and drug use, from 1999 to 2010. To achieve the proposed objectives I used different methodological procedures, such as theoretical research on the violence theme, crime, fear, security and crime prevention. I collected data and informations about violent crimes in various government agencies, specifically in the Health Ministry and the Operations Center of Military Police, located in Uberlândia. I did semi-structured interviews with residents, aiming to understand how they view and behave in violence context. I mapped the violent crime in urban scale, highlighting the neighborhoods where the records were more pronounced in the period in question. According the research, the main victims of crimes against morals (rape) and against the person (homicide) are mainly children, teenagers and young people. For the rape cases, the most affected age group is between 10 and 19 years old, with girls being the most victimized. About the homicides, it affects teenagers and young males, in age between 20 and 29 years old. In crimes against property (robberies), the highlight concentrated against pedestrians, vehicles, stores, public bus and bicycle. Drug trafficking is increasing at Uberlândia, with respective growing in number of users. Also, prisons and seizures are answers to effective strategies in combat to traffic, but similarly showing that organized crime has expanded its influence. Against the violent crime in the city, there are several preventive measures in development, with positive results, especially the Programa Fica Vivo, aimed to the homicides preventions and the Sistema Olho Vivo de Videomonitoramento, installed in neighborhoods Central Sector to contain mainly robberies. Other actions are being developed in schools, aimed to children, teenagers and young people education about the consequences of drugs involvement, such as homicides, the main violent crime related to trafficking. To think the violence and the prevention and its control is not easy because this question has a multifaceted dynamic and character. However, I observe successful strategies in level intersectoral and interdisciplinary approach, involving professionals from various fields. This is therefore the effective way of thinking, support and manages public safety policies: from the identification of priority areas it is possible establish integrated actions aimed to controlling and preventing of violent crime.